Rumah Sakit Paru-Paru Di Pekanbaru Dengan Pendekatan Arsitektur Hi-Tech - Qaris, Fuzail; Hidayat, Wahyu; Novan, Andre (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The phenomenon of forest fires in Riau resulted in a smoke disaster that became the main problem every year. Uncontrolled forest fires are air pollutants that can interfere with daily activities and are also harmful to respiratory health. As a result, many of Riau residents are experiencing respiratory health problems caused by the smoke disaster, especially in Pekanbaru. Therefore, it is necessary to present a special health facility to treat lung abnormalities, namely Lung Hospital in Pekanbaru. Successful healing of lung disease depends on a natural, healthy, clean, and pollution-free environment. Thus, the Hi-Tech design approach was chosen to be able to engineer the environment to keep the air clean and pollution-free in the event of a smoke disaster. The application of technology to the building focuses on natural air-conditioning systems in the hospital environment as a healing medium for patients. This building is expected to help the healing process of the patient so that the concept applied is Hospital, Healthy House. This concept is transformed into a healthy zoning, healthy space, healthy accessibility, and a healthy facade. The results of this study in the form of Lung Hospital design that applies technology as an effort in assisting patients in the healing process of lung disease.Keywords: Lung Hospital, Pekanbaru, Hi-Tech, Healthy House